IMPLEMENTASI PEMBERIAN BAKTERI RHIZOBIUM SPP DENGAN PENAMBAHAN PUPUK ORGANIK DARI KOTORAN KAMBING PADA PROSES PERTUMBUHAN TANAMAN SORGUM (Sorghum bicolor L.) - Widodo, Tirto Wahyu; Muhklisin, Ilham; Setyo Andi Nugroho; Perkasa, Indra Jaya (JURNAL BIOSENSE, 2024)
Rhizobium spp. bacteria can associate with non-legume plants, such as sorghum. The potential for Rhizobium spp. in association with sorghum can be enhanced by adding organic materials like goat manure. This study aims to examine the influence of Rhizobium spp. The research was conducted using a factorial Completely Randomized Design (CRD) consisting of two factors and three replications. The first factor included control treatment (without Rhizobium spp.), Rhizobium spp. from the rice root zone, Rhizobium spp. from the corn root zone, Rhizobium spp. from the edamame root zone, Rhizobium spp. from the soybean root zone, and Rhizobium spp. from the peanut root zone. The second factor was the dose of goat manure fertilizer, which consisted of 140 g/polybag, 210 g/polybag, and 280 g/polybag. The results showed an increase in root absorption capacity. Rhizobium spp. from the non-legume root zone had a significant effect compared to Rhizobium spp. from the legume root zone on plant height (210 cm), number of leaves (17), and stem diameter (34.17 mm). This is thought to be because Rhizobium spp. from the non-legume root zone adapts more easily to the sorghum root zone. Rhizobium spp. from the non-legume root zone (graminae) with 280 g of goat manure per polybag had a significant effect on stem diameter (34.17 mm).